A Report from a Workshop of the International Stem Cell Banking Initiative, Held in Collaboration of Global Alliance for iPSC Therapies and the Harvard Stem Cell Institute, Boston, 2017. (6th August 2019) - Kim, Jung‐Hyun; Alderton, Alex; Crook, Jeremy M.; Benvenisty, Nissim; Brandsten, Catharina; Firpo, Meri; Harrison, Peter W.; Kawamata, Shin; Kawase, Eihachiro; Kurtz, Andreas; Loring, Jeanne F.; Ludwig, Tenneille; et al.
Abstract: This report summarizes the recent activity of the International Stem Cell Banking Initiative held at Harvard Stem Cell Institute, Boston, MA, USA, on June 18, 2017. In this meeting, we aimed to find consensus on ongoing issues of quality control (QC), safety, and efficacy of human pluripotent stem cell banks and their derivative cell therapy products for the global harmonization. In particular, assays for the QC testing such as pluripotency assays test and general QC testing criteria were intensively discussed. Moreover, the recent activities of global stem cell banking centers and the regulatory bodies were briefly summarized to provide an overview on global developments and issues. Stem Cells 2019;37:1130–1135 Abstract : Photo of the 2017 Boston meeting, celebrating 10 years of International Stem Cell Banking Initiative activities.